APPLICATION OF DZIKIR THERAPY ON MRS. P, A HYPERTENSION PATIENT WITH ANXIETY NURSING PROBLEMS IN GARUDA HOUSING AREA RT 43, JAMBI IN 2023 - Sodikhoh, Jamiatus; Yuliana, Yuliana (Jurnal Pinang Masak, 2023)
Background: Anxiety is a vague fear and cannot be supported by situations. Excessive anxiety has a detrimental effect on the mind and body and can even cause physical and psychological illnesses. So management or treatment is needed not only pharmacologically but also non-pharmacologically. Non-pharmacological management of anxiety includes deep breathing techniques, distraction, five-finger hypnosis and dhikr therapy. Method: Case study with data collection techniques through observation, interviews and physical examination. Results: From this study, it was found that after the client had performed dhikr therapy for four days, the anxiety experienced by the client decreased from severe to moderate anxiety levels. So the application of dhikr therapy is effective in reducing anxiety. Conclusion : Based on the evaluation after the dhikr therapy and deep breathing techniques were carried out in the case, it was found that anxiety decreased from severe to moderate. From the research, it was found that the benefits of dhikr therapy are putting a response in the form of calm, and reducing the level of anxiety.